'Same storm, different boats': the COVID-19 pandemic and its impact on Indonesian public companies. (17th January 2023) - Fahlevi, Heru; Syukur, Muhammad
This study aims to evaluate the financial performance of Indonesian public companies before and during the COVID-19 pandemic. Data were collected from the Osiris database. Net income and return on assets (ROA) were used as proxies of financial performance, and the current and solvency ratios were also evaluated. Using the Wilcoxon signed-rank test and Pearson correlation test, this study found a significant difference in financial performance before and during the first year of the pandemic. The results show that 337 companies (68%) experienced a reduction in net income in 2020, while 115 companies (31%) recorded unchanged or even higher profits. Although this study found a statistical difference between the financial indicators before and during the pandemic, not all companies recorded a worse financial performance. Before the pandemic, those with substantial assets and stronger financial performance tended to experience only a minor profit reduction and higher net income in 2020.